A cross-sectional study on hospital-based evaluation of adverse drug reactions and drug-related issues in hypertensive patients - Aqsa Khan; Alhamd Tanveer; Amisha Vohra; Tooba Amin Khan; M. Sohel Akhter; Abhishek Goyal; M. Afroz Ahmad; M. Nematullah (International Journal of Basic & Clinical Pharmacology, 2026)
Background: The primary goal of the study was to evaluate adverse drug reactions and drug-related problems in patients with hypertension at the tertiary care hospital in Lucknow. The secondary goal was to assess the treatment patterns and outcomes for these patients at the same hospital. Methods: This was a prospective, observational study. A total of 100 patients who met the inclusion and exclusion criteria were recruited from the outpatient and inpatient departments of the general medicine division at the Integral Institute of Medical Science and Research Hospital. Patients’ data were evaluated to identify Drug-Related Problems using a systematic, evidence-based approach. Results: Data from 100 patients were collected in this study. The main identified drug-related problems affecting blood pressure control included failure to receive medications, drug-drug interactions and untreated indications. A total of 3 adverse drug reactions (ADRs) were observed among the 100 cases. Hyperkalemia was observed in 02 patients (28.6%), pedal edema in 02 patients (28.6%) and dry cough in 03 patients (42.9%). Conclusions: Patients taking anti-hypertensive medications frequently encounter adverse drug reactions. Our study recommends regular ADR monitoring in hospital settings to encourage rational medication prescribing.